2009
DOI: 10.1111/j.1610-0387.2008.06919.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacoeconomic model of topical treatment options of mild to moderate psoriasis vulgaris in Germany

Abstract: The treatment of mild to moderate psoriasis with a fixed calcipotriol/betamethasone combination is a more cost-effective treatment than a treatment with the single agents or tacalcitol monotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 25 publications
0
8
0
3
Order By: Relevance
“…It can therefore be expected that the use of biologics, including UST, will continue to increase with the use of conventional therapies. This trend is currently observed in many countries [37] and believed to result from increased awareness among dermatologists of psoriasis as a significant medical condition that strongly impacts the quality of life and the availability of guidelines and concepts on treatment goals, which support a consequent treatment of affected patients [38]. …”
Section: Five-year Viewmentioning
confidence: 99%
“…It can therefore be expected that the use of biologics, including UST, will continue to increase with the use of conventional therapies. This trend is currently observed in many countries [37] and believed to result from increased awareness among dermatologists of psoriasis as a significant medical condition that strongly impacts the quality of life and the availability of guidelines and concepts on treatment goals, which support a consequent treatment of affected patients [38]. …”
Section: Five-year Viewmentioning
confidence: 99%
“…According to the 18 studies where we found a definite or potential impact of uncertain variables or assumptions on the final conclusions, the key drivers included (1) the costs of the medication or phototherapy itself, or related assumptions such as dosage, a treatment-free response period, average wholesale price, and weight and waste of excess medications [21,24,27,34,40,43,46,50,51,61,62,71]; (2) the values of efficacy measures, which include PASI response rate, DLQI response rate (a minimally important difference [MID]), clearing rate, response rate achieved in re-treatment [23,26,27,34,40,46,59,61], and the choice of efficacy measures, PASI 75 or DLQI MID [34]; (3) utility values, which comprised of those with different disease severity levels or PASI response health states, baseline utility values, and utility ratings for side effects, or being on the waiting list [22,26,51,57,67]; (4) hospitalization assumptions for non-responders [24,62,67]; (5) considering lost productivity during hospitalization [62]; and (6) different time horizons [40]. …”
Section: Within the Studymentioning
confidence: 99%
“…Bereits in 2009 zeigten Augustin et al [3], dass das Kombinationspräparat (Bet/Cal) effektiver und kostengünstiger sei im Vergleich zu den Einzelsubstanzen oder Tacalcitol allein. Wie sich der konsequente Erstlinieneinsatz auf das entsprechende Budget der einzelnen Praxen auswirkt, wird sich zeigen.…”
Section: Transfer In Die Praxis Von Dr Sandra Philipp (Oranienburg)unclassified